Os impactos da satisfação no trabalho: uma análise da qualidade de vida do trabalho de acadêmicos do curso de Administração da UFAM - Pacheco, Larissa Soares (Brasil, 2024)
The research aims to answer how satisfaction in the corporate environment impacts the quality of work life of students on the Administration course at a federal institution, who work full-time or perform some type of work. To achieve this objective, the concepts of job satisfaction and Quality of Work Life (QWL) are addressed. The methodology adopted for analysis is quantitative, using validated questionnaires based on Richard Walton's model, widely recognized and adapted for this study, followed by a descriptive statistical analysis of the data collected. The results reveal that the majority of university students consider themselves satisfied in relation to most aspects related to QWL. However, the points of greatest dissatisfaction are concentrated in professional fulfillment, low salaries compared to their colleagues, internal relationships within the organization, the perception of little appreciation of career and skills, and the lack of progression opportunities. These factors play a crucial role in evaluating QWL, since satisfaction is a fundamental indicator of this aspect.